The MCCC Volunteers' Legacy of Approaches for Combating COVID-19 - Hayati, Afita Nur; Akhyar, Ramadiva Muhammad; Aini, Amalia Nur; Setyowati, Dina Lusiana; Yatini, Yatini (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
As one of the Penta Helix elements in crisis management, Muhammadiyah conducted humanitarian efforts throughout the pandemic, notably in East Kalimantan, through the Muhammadiyah COVID-19 Command Center (MCCC). As a collective humanitarian memory of East Kalimantan during the height of the COVID-19 pandemic, this study attempts to present an overview of all the volunteer activities conducted by MCCC in Balikpapan and Samarinda during the pandemic. Descriptive analysis and qualitative technique are utilized in this study. To gather primary data, two informants from Balikpapan and four informants from Samarinda were interviewed. Secondary data came from reporting documents from the Muhammadiyah Disaster Management Center (MDMC) in East Kalimantan, which were located through a Google search for pertinent terms. The following are the study's findings: (1) In Balikpapan and Samarinda, MCCC volunteers took part in emergency response and disaster risk mitigation operations. (2) They give medical aid, apply disinfectants, and conduct out programs related to food security. (3) They go a long way to help others. They are all living examples of that since they have all survived COVID. During the peak of the COVID-19 pandemic, one individual was hospitalized, others were forced to self-isolate, and there were no reports in the media about any philanthropic activities. In conclusion, as volunteers are at high danger during the COVID-19 pandemic, their goodness cannot be questioned.